2019
DOI: 10.1038/s41598-019-48309-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional alterations reveal Bacillus amyloliquefaciens-rice cooperation under salt stress

Abstract: The Bacillus amyloliquefaciens -SN13 and model crop rice ( Oryza sativa ) were chosen to understand the complex regulatory networks that govern plant-PGPR interaction under salt stress. During stress, inoculation with SN13 significantly increased biomass, relative water content, proline and total soluble sugar in rice while decreased lipid peroxidation and electrolyte leakage. Extensive alterations in gene expression were also observed in rice root transcriptome un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“… Area of the total agricultural land in different continents that has sodic and saline soil (in millions of hectares of land) ( FAO, 2019 ; Chauhan et al, 2019 ). …”
Section: Introductionmentioning
confidence: 99%
“… Area of the total agricultural land in different continents that has sodic and saline soil (in millions of hectares of land) ( FAO, 2019 ; Chauhan et al, 2019 ). …”
Section: Introductionmentioning
confidence: 99%
“…Further, PGPR have also been reportedly used as biofertilizers, due to their ability to enhance crop yields and soil fertility through the nutrient cycle between the plant roots, soil and microbes [ 12 , 13 , 14 , 15 ]. Modulations of multiple gene expression and changes in plant physio-chemical, cellular and molecular pathways were also due to complex interactions between plants and PGPR [ 6 , 16 , 17 , 18 ]. MicroRNAs (miRNAs), which are 20- to 24-nt non-coding small RNAs, regulate the expression of their target genes either by the cleavage or translational repression of target genes [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A transcriptome of rice plants inoculated with Bacillus amyloliquefaciens SN13 showed that the bacterial inoculation alters gene expression under salt stress. For example, genes of phytohormones, flavonoids, or photosynthesis are found in higher number in inoculated plants [104]. Other example is the inoculation of wheat with Dietzia natrolimnaea that causes an overexpression of genes involved in the ABA signaling cascade and in the salt sensitive pathway among others [105].…”
Section: Molecular Mechanisms In the Bacteria-plant Interactions Undementioning
confidence: 99%